MEDIA EVOLUTION AND THE IMPACT OF DIGITALISATION ON TELEVISION - Georgiana Stanescu (Social Sciences and Education Research Review)
The article examines the radical transformations in the media industry that have occurred over the last years under the influence of the development of online platforms and digitalization. First, the article explores how access to news and media content has evolved from television to online platforms and social networks. It discusses how TVs have responded to this change by creating online news and content sites and adapting to the social environment. It also highlights the importance of active user participation in the production and distribution of media content influenced by new technologies such as virtual reality and artificial intelligence. In conducting the research, we used the quantitative method by applying a questionnaire on a Likert scale from 1 to 5, where 1 is total disagreement, and 5 is total agreement. The questionnaire was applied to the general public consumers of media content. The conclusion is that the public is increasingly turning to online media and consuming less content from traditional media outlets. In this context, broadcasters have increasingly had to adapt to this trend. The article is useful mainly for researchers but also the industry.